PENINGKATAN KETERAMPILAN MENGANALISIS UNSUR INTRINSIK CERPEN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD SISWA KELAS X.A SMA NEGERI 1 LIRIK KABUPATEN INDRAGIRI HULU TAHUN PELAJARAN 2013/2014 - -, SRI ANDRAFITA (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Purpose of this research that is how improving skill the analysis and any kind ofinfluencing change result of learning to analysis of intrinsic short story of class X.A SMANegeri 1 Lirik Regency Indragiri Hulu. One of study method read systematic and effective toactive, developing interest and able to improve ability analysis the understanding of studentSMA Negeri 1 Lirik method STAD (Student Teams Achievement Division).This research trough Class Action Research (CAR). This research using qualitativeapproach. The subject of the research is the students of X.A SMA Negeri 1 Lirik RegencyIndragiri Hulu totally 20 students. This research was conducted on Mey 2014, consist of twocycles, one in twice meeting.The research showed that learning cooperative STAD model can improve the activitiesprocess of students including pay attention to the teacher explanation, study in group, makingpresentation, making questions, and answer questions. the increasing students learning can beseen from the average of learning result cycles I 72,3%, on sycles II increase 85,2%. Theconclusion of this research is STAD model can increase the activity and students achievementon analysis the understanding of student X.A SMA Negeri 1 Lirik Regency Indragiri Hulu.